Effectiveness of African Bitter Leaf (Vernonia amygdalina) on Blood Sugar Level among Diabetic Clients: A Systematic Review of Randomized Controlled Trials - Kumar, Ray Suresh (Journal of Neonatal Surgery, 2025)
Background: African bitter leaf (Vernonia amygdalina) is widely used in many African settings as a food vegetable and traditional remedy for diabetes. However, clinical recommendations should rely on randomized evidence in diabetic patients rather than on preclinical findings or anecdotal use. Objective: To systematically review randomized controlled trials (RCTs) evaluating the effectiveness of African bitter leaf on blood sugar outcomes among diabetic clients. Methods: This review was structured in line with PRISMA 2020 reporting guidance. Searches were conducted through 03 July 2026 across Google Scholar, PubMed-indexed records, PubMed Central, African Journals Online, journal websites, and supplementary web sources using combinations of “Vernonia amygdalina,” “African bitter leaf,” “bitter leaf,” “diabetes,” “diabetic,” “randomized,” “trial,” and glycaemic outcome terms. Eligible studies were RCTs enrolling participants with diabetes and reporting blood glucose outcomes after oral administration of bitter leaf preparations. Animal studies, in vitro studies, reviews, observational studies, and studies in non-diabetic volunteers were excluded. Results: No eligible RCTs involving diabetic clients were identified. The searchable literature was dominated by animal studies, mechanistic studies, and narrative reviews. One accessible human randomized-order acute feeding study enrolled 16 normoglycaemic adults rather than diabetic patients and therefore did not meet the review question. That study reported lower postprandial glucose responses after 50 g Vernonia amygdalina compared with another indigenous vegetable comparator over 2 hours, but its findings cannot be generalized to diabetic clients. Contemporary reviews published in 2019, 2023, 2024, and 2025 consistently describe a major lack of clinical trials in diabetic patients. Because no eligible RCTs were found, risk-of-bias appraisal and meta-analysis were not undertaken. Conclusion: There is currently no randomized clinical evidence to confirm that African bitter leaf improves blood sugar control among diabetic clients. Until well-designed human RCTs are completed, bitter leaf should not be recommended as an evidence-based glucose-lowering therapy in place of standard diabetes care....